Fabrication of carbon nanofibrous microelectrode array (CNF-MEA) using nanofiber immersion photolithography (2014)
Microelectrode arrays (MEAs) are widely used for stimulating and receiving electrical signals between human and machines and for in vitro neural study. This work demonstrates the fabrication process of nanofibrous 3D microelectrodes using immersion lithography. Oil immersion negates the diffraction effects intrinsic in the photopatterning of electrospun nanofibers to give increased aspect ratio microarchitectures. Nanofiber electrode resistivity is characterized and its performance compared to that of carbon thin film. In vitro testing of electrodes are performed using E18 cortical neurons and analyzed for cell density and cell viability. © 2014 IEEE.